Centralised or decentralised public financing of clusters. Issue 2 (3rd March 2016) - Urbančíková, Nataša; Burger, Peter
Abstract: The public funds have become a major source of finance for clusters in the last decade, also in European countries. The source of financing clusters and innovation performance of the countries is directly connected to subjects of the national/regional cluster policy, i.e. to its centralisation. The paper examines the relationship between European country attitude towards financial support provided for cluster and country innovative performance in a sample of 125 clusters from 25 European countries. The own empirical investigation is based on primary research using the Kruskal-Wallis test and Mann-Whitney tests with Bonferroni. The investigation is focused on facts whether statistically significant differences in the amount of subsidies from national, regional, local and "European" levels between clusters in European countries influence their level of innovation performance. The finding shows that there are no statistically significant differences in the exploitation of resources from the Structural Funds and community programmes of the EU in the examined clusters in the countries with different levels of innovation performance. However, the clusters in the countries with higher levels of innovation performance receive funds in the form of central government and regional self-government subsidies more frequently than the clusters in the countries with lower levels of innovation performance.